(untitled) (Research, Society and Development, 2021)
It was analyzed, from the perspective of the manager and health professionals, a methodological proposal for working in groups to promote adequate and healthy eating (Promoção da Alimentação Adequada e Saudável – PAAS, in portuguese) in Primary Health Care based on Paulo Freire’s framework. This is a qualitative study, in which interviews were conducted using a semi-structured script and, later, transcribed and analyzed using the content analysis technique. Participants positively rated the PAAS group methodology for its practical applicability; by valuing the user as an autonomous subject and protagonist of care; for allowing adaptations to various themes, including those outside the field of Nutrition; and for constituting an educational approach that distances itself from the traditional one based on expository classes. Additionally, the fragility of the training and qualification processes of professionals to conduct collective educational activities in the emancipatory perspective of the subjects and the influence of the biomedical model in the organization of the health services in which they work became clear. Innovative and active methodologies, as analyzed here, can be useful in improving collective actions to promote health and adequate and healthy eating.